Chasing the light : writing, directing, and surviving Platoon, Midnight Express, Scarface, Salvador, and the movie game /: writing, directing, and surviving Platoon, Midnight Express, Scarface, Salvador, and the movie game. (2020) - Stone, Oliver
No abstract available